Life Narratives of Adults with Obsessive-Compulsive Disorder in Galle Area: An Explorative Study - Vithana, K.V.G.S.G.; Boralessa, P.; Asurakkody, T.A.; Perera, D.P. (My University, 2022)
Introduction: Obsessive-compulsive disorder (OCD) is a greater prevalent and debilitating psychological health disorder known to influence various life domains. Yet little is known about the subjective narratives of living with OCD amongst Sri Lankans and the ways in which it impacts to daily life. Objective: Toexplore the life narratives of adult individuals diagnosed with OCD within the Galle area in Sri Lanka with a focus on the impact of OCD on their life. Methods: Qualitative phenomenological study selected a purposive sample of ten adults primarily diagnosed with OCD who were registered in psychiatric clinics in Teaching Hospital, Karapitiya, Sri Lanka. Data was collected from April to July 2021 to take part in semi-structured interviews. Interviews were audio recorded and transcribed verbatim. Verbatim was analyzed thematically. Results: Overall, four main themes and 11 sub-themes were illustrated which comprised a) Direct impact to self - coping strategies, sleep and cognitive impairment b) Living with family - various reactions from family, family members’ perception c) Influences on academics and work- impairment productivity of work or academic progress, communication issues in work or academic environment. d) Social and cultural impact- socializing issues, cultural influences and religious impact and support from society. The individuals viewed OCD as a disorder that unfavorably influenced their life. They become at risk of interrupting continuing treatments, with the possibility of enhanced severities or recurrences of symptoms in OCD. Conclusions: Adults with OCD with OCD have issues with their life related to self, family, work, academic and socio-cultural aspects of their life. Findings can be used as basis for develop of interventions that meet the person needs and attention to increase quality of life. Findings will help to arrange supportive programs to adjust treatment and nursing strategies with community nursing programs.
Keywords: Adults; Obsessive-Compulsive Disorder